ENERGY SECTOR OF INDIA: PAST AND PRESENT - K. A. Ibragimova (Vestnik MGIMO-Universiteta, 2017)
Strengthening the influence of India in the Asian region and in the world requires for resorting of the modernization experience of this country, including the development of its energy sector. India today is among the top ten countries to generate electricity per capita. At the same time, both traditional sources of energy production coexist in India (using the muscular strength of man and animals) with the conditions for the development of modern energy infrastructure through foreign investments. The article attempts to trace the main stages of the formation and development of energy industry in India; the modern state of energy is analyzed and plans for its development are considered. The research is based on a complex of traditional methods and approaches based on the principle of scientific objectivity and systemic method used in research in the framework of international relations and political science. For more than a century of history of the development of energy sector in India significant success has been achieved. Starting with the electrification of large cities and industrial enterprises due to foreign investments in the colonial period, India, after gaining the independence, set the task of developing its own infrastructure, electrifying the countryside and providing the industry with energy resources. The greatest progress in the development of electric power and nuclear energy was made. Indian economic growth will increase India’s energy needs and quadruple the demand for electricity over the next 25 years. For this, India needs to solve the problems of energy efficiency, energy complex management, lack of standards and energy imports, as well as actively introduce alternative energy sources and move to clean electricity (increased use of water resources and solar energy), which can be done through the development of Russian -Indian cooperation.